STUDY THE POTENTIAL ANTIOXIDANT EFFECT OF VITAMIN D3 SUPPLEMENTATION ON THE LEVEL OF EXTRACELLULAR SUPEROXIDE DISMUTASE IN ASTHMATIC PATIENTS - Abbas, Rasha Saadi; Abdulridha, Manal Khalid; Shafek, Mostafa Abdalfatah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was designed to evaluate the potential antioxidant effect of vitamin D3 supplementation in chronic asthma patients. Methods: A total of 44 candidate patients were diagnosed with asthma allocated as Group 1 includes 20 patients assigned to receive conventional therapy for asthma and Group 2 includes 24 patients assigned to receive conventional therapy for asthma plus 2000 IU vitamin D3 tablet for 3-month period. Furthermore, 30 apparently healthy subjects were included in the study as a control group. Pulmonary function test, serum 25-hydroxy vitamin D levels, serum extracellular superoxide dismutase (SOD3) levels were measured before and after 3 months therapy. Results: The mean forced expiratory volume in 1 second (FEV1) both the measured and the percentage of predicted value showed a highly significant increase after 3 months treatment compared to pre-treatment value in both study groups (p<0.01). When compared to pre-treatment value, there was no significant increase in forced expiratory volume in one second to forced vital capacity ratio (FEV1/FVC) in Group 1 (p>0.05), nevertheless, Group 2 showed highly significant increase after 3 months (p<0.01). Approximately, 90-96% of adult asthmatic patients revealed vitamin D deficiency (<20 ng/ml). Post-treatment with adjuvant vitamin D3 therapy, 25% of patients obtained acceptable level of vitamin D sufficiency (â‰¥30 ng/ml). After 3 months of the treatment, Group 1 patients showed a significant decrease in mean SOD3 level compared to pre-treatment level (p<0.05), while Group 2 patients showed a significant increase in mean SOD3 level compared to pre-treatment level (p<0.05). Conclusion: Most of the asthmatic patients revealed vitamin D deficiency and supplementation with vitamin D3 reduce oxidative stress burden in those patients.